Of human bondage - Davis, Bette, 1908-; Howard, Leslie, 1893-1943.; Cromwell, John, 1888-1979.; Maugham, W. Somerset 1874-1965. (Woodland Hills, CA : Westlake Entertainment Group, 2004)
The poignant story of a cripped medical student's feverish love for a sluttish waitress.
Based on the novel by Somerset Maugham.
Videocassette release of the 1934 motion picture.
Bette Davis, Leslie Howard, Frances Dee, Kay Johnson, Reginald Denny, Alan Hale, Reginald Owen.
DVD.
Keywords: Feature films